Thresholds of Cytoprotection: Ethanolic Propolis Extract Mitigates Ischemia-Reperfusion Injury via the MDA/IL-6 Axis in a Graded Rat Skin Flap Model - Dinar Kukuh Prasetyo; Amru Sungkar; Brian Wasita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Distal necrosis in reconstructive skin flaps results from ischemia-reperfusion (I/R) injury, driven by reactive oxygen species (ROS) and pro-inflammatory cytokines. While Propolis exhibits antioxidant properties, its efficacy limit relative to the severity of ischemic challenge remains undefined. Methods: A randomized, controlled experimental study was conducted using 36 male Wistar rats. A graded ischemia model was engineered using modified McFarlane flaps with increasing length-to-width ratios: Mild (2:1), moderate (3:1), and severe (4:1). Subjects were stratified into vehicle (Control) and treatment (Propolis 800 mg/kg/day, oral) groups across all dimensions. The primary endpoint was the percentage of viable flap area on Day 7. Secondary endpoints included serum Malondialdehyde (MDA), Interleukin-6 (IL-6), and histological scoring of inflammation. Results: All animals survived the procedure. Propolis significantly increased viable tissue area in the moderate ischemia group (76.4 ± 4.2%) compared to Vehicle (52.1 ± 5.8%; p < 0.001). In Mild ischemia, survival was near-maximal in both groups (>92%). However, in Severe ischemia, Propolis failed to prevent significant necrosis (34.2 ± 6.1% survival vs. 28.5 ± 5.4% in Vehicle; p = 0.092), indicating a therapeutic ceiling. Biochemically, Propolis suppressed MDA (11.92 ± 0.45 nmol/mL) and IL-6 (121.0 ± 4.71 pg/mL) significantly in moderate challenges but was overwhelmed by the oxidative surge in severe ischemia (MDA > 12.0 nmol/mL). Conclusion: Propolis confers significant protection against I/R injury by dampening lipid peroxidation and systemic inflammation, but this effect exhibits a distinct threshold. It is highly effective in moderate ischemic challenges but insufficient for severe vascular compromise.